Pengembangan Destinasi Mice Kota Cirebon dalam Perspektif Pariwisata Berkelanjutan - Dirgantara, Ahmad Rimba; Febriana, Febriana (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2020)
The Indonesian economy which experienced positive growth in the last few years has had a positive impact on the development of various other industrial sectors. One that is experiencing significant development is the MICE industary (meetings, incentives, conferences and exhibitions). The MICE industry has an impact on the economy in the form of increased incomes, expanding employment and employment opportunities, and encouraging investment. Cirebon City as part of the Province of West Java has the potential to become one of the MICE venue on a national and international scale. However, development constraints such as infrastructure, workforce readiness, and other driving factors must still be addressed so that the development of MICE destinations can develop in a sustainable manner. The purpose of this research is to provide an example of sustainable tourism through the MICE tourism concept. The methodology in this study uses descriptive analysis by analyzing documents related to the development of Cirebon City MICE through the perspective of sustainable tourism. The results of this study show that the development of the Cirebon City MICE destination is in line with the perspective of sustainable tourism with the following recommendations; reviewing the physical feasibility of the environment, economic viability, and socio-cultural viability.